The bioactivities of sclareol: A mini review - Zhou, Jianbo; Xie, Xiaofang; Tang, Hailin; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2022)
Sclareol, a diterpene alcohol isolated from the herbal and flavor plant clary sage (Salvia sclarea L.), is far-famed as the predominant ingredient in the refined oil of Salvia sclarea (L.). The empirical medicine of Salvia sclarea L. focused on various diseases, such as arthritis, oral inflammation, digestive system diseases, whereas the sclareol possessed more extensive and characteristic bioactivities, including anti-tumor, anti-inflammation and anti-pathogenic microbes, even anti-diabetes and hypertension. However, there is a deficiency of literature to integrate and illuminate the pharmacological attributes of sclareol based on well-documented investigations. Interestingly, sclareol has been recently considered as the potential candidate against COVID-19 and Parkinson’s disease. Accordingly, the bioactive attributes of sclareol in cancer, inflammation, even pharmacochemistry and delivery systems are reviewed for comprehensively dissecting its potential application in medicine.